Affective value and associative processing share a cortical substrate - Shenhav, Amitai (2013)
The brain stores information in an associative manner so that contextually related entities are connected in memory. Such associative representations mediate the brain’s ability to generate predictions about other objects and events to expect in a given context. Likewise, the brain encodes and is able to rapidly retrieve the affective value of stimuli in our environment. That both contextual associations and affect serve as building blocks of numerous mental functions often makes interpretation of brain activation ambiguous. A critical brain region where such activation has often resulted in equivocal interpretation is the medial orbitofrontal cortex (mOFC), which has been implicated separately in both affective and associative processing. To characterize its role more unequivocally, we tested whether activity in mOFC was most directly attributable to affective processing, associative processing, or to a combination of both. Participants performed an object recognition task while undergoing fMRI scans. Objects varied independently in their affective valence and in their degree of association with other objects (associativity). Analyses revealed an overlapping sensitivity whereby left mOFC responded both to increasingly positive affective value and to stronger associativity. These two properties individually accounted for mOFC response, even after controlling for their interrelationship. The role of mOFC is either general enough to encompass both associations that link stimuli with reinforcing outcomes and with other stimuli, or abstract enough to use both valence and associativity in conjunction to inform downstream processes related to perception and action. These results may further point to a fundamental relationship between associativity and positive affect.